Basal Ganglia Disease and Visuospatial Cognition: Are There Disease-Specific Impairments? - Erich Mohr; Jules J. Claus; Pim Brouwers (Behavioural Neurology, 1997)
Visuospatial deficits in basal ganglia disease may be a non-specific function of the severity of dementia or they could reflect disease-specific impairments. To examine this question, Huntington (HD) patients, demented and non-demented Parkinson (PD) patients and healthy controls were examined with neuropsychological tests emphasising visuospatial abilities. Global intellectual function and general visuospatial cognition were less efficient in the two demented patient groups relative to both controls and non-demented PD patients and they did not differ significantly between non-demented Parkinsonians and controls nor between demented PD and HD patients. However, HD patients but not demented PD patients were impaired on a test of person-centred spatial judgement compared to non-demented subjects while demented PD patients scored significantly lower than HD patients on a test of field independence. Factor analysis yielded a factor reflecting general visuospatial processing capacity which discriminated between demented and non-demented PD patients but not between demented PD and HD patients. A unique factor associated with the manipulation of person-centred space discriminated between demented PD and HD patients. These results suggest general visuospatial processing is impaired as a non-specific function of dementia presence in HD and PD. Abnormalities in circumscribed aspects of visuospatial function, on the other hand, may differentiate between HD and PD, suggesting differential involvement of the basal ganglia in the respective illnesses.